MODEL BELAJAR DAN PEMBELAJARAN BAHASA ARAB GENERASI MILENIAL - Akhsan Akhsan; Ahmadi Muhammadiyah (Fakultas Tarbiyah Universitas Ibrahimy, 2020)
Millennial era is identical with digital era. Where millennials are more inclined to like learning with practical and rational. Millennials prefer something simple and not complicated. Indirectly with this it also affects the learning styles of Arabic students. With this fact, the language teacher must also adjust to technology. In the midst of the covid-19 pandemic, literacy learning models, hybrid learning, and long life learning become learning models that are always discussed and discussed in various forms. Literacy with a genre approach, hybrid learning with online models and webinars, as well as long live education by planting lifelong learning to students wherever they are. These three things are expected to have a significant influence on learning and learning models in this millennial era. Especially in a pandemic that does not allow for face-to-face meetings, so it is more efficient, practical, and effective.